Pengaplikasian Konsep Bimbingan Konseling dalam Belajar dan Pembelajaran : (Studi Kasus SMP Negeri 10 Medan) - Eduard Steven (Institute of Computer Science (IOCS), 2021)
This research aims to find out the need for the application of the concept of Guidance and Counseling in teaching and learning activities in SMP Negeri 10 Medan., the ability and understanding of classroom teachers in applying the concept of Guidance and Counseling in teaching and learning activities in SMP Negeri 10 Medan., How the intensity of the application of guidance and counseling concepts in teaching and learning activities in SMP Negeri 10 Medan. The sample in this study is a classroom teacher found in SMP Negeri 10 Medan which amounted to 31 teachers who served in SMP Negeri 10 Medan., the data analysis technique used is content analysis or non-statistical analysis. Based on the data analysis, the results of the study are obtained as follows: In general, students in junior high school also urgently need Guidance and Counseling in teaching and learning activities., in general, teachers who serve in SMP Negeri 10 Medan, have understood and applied the concept of Guidance and Counseling in teaching and learning activities. well, career guidance in the category is quite good, the application of tutoring and the application of social guidance in the category is not good., in general, the reality of teachers who serve in SMP Negeri 10 Medan expects a special officer of Guidance and Counseling (BP teacher/Counselor).